The TRAIL map - Jan-Peter Sandler; Maryvonne Nieboer; Branko Anđić; Luca Corazzini; Ella Cosmovici Idsøe; Nina Troelsgard Jensen; James McGeever; Marca Wolfensberger; Anne-Mieke Vandamme (Journal of the European Honors Council, 2025)
Human development has spurred hypercomplex issues like pandemics and climate change, unmanageable through STEM-alone approaches. Addressing these demands collaboration across academic (including non-STEM disciplines) and non-academic fields, necessitating a transdisciplinary approach. Higher education should cultivate 21st-century skills, like those in TRAnsdisciplinary Innovation Labs (TRAIL), enabling adept collaboration on multifaceted problems within diverse groups.